Promoção da qualidade de vida dos idosos portugueses através da continuidade de tarefas produtivas - Gonçalves, Daniela (2013)
The current demographic circumstances and its consequences in the social system, from family relationships to the functioning of the macro structures, as well as health care, makes it necessary to reconsider the elder's role in the Portuguese context. To promote life quality when physical decline is inevitable implies considering multidimensional criteria, such as maintaining the social network and significant activities. The productive aging theory emphasizes both the contributions that elders can give to society, through the goods they produce, as well as the well-being and life quality that come from this process (Kaye, Butter & Webster, 2003). However, in Portugal there is still no planning for the implementation of strategies that can direct and promote the use of the resources that elders can give, which is something that needs to be modified.